Penyelenggaraan Pemerintah Daerah di Kabupaten Tapanuli Tengah - Novan Andreas.L. Tobing (Dinamika Politik, 2013)
This study is the study of the organization of Local Government in Central Tapanuli Regency Focus discusses the implementation of Local Government whether conditions in Central Tapanuli goes well with the Law No. 32 of 2004. Findings of this study include local governance conditions in Central Tapanuli Regency is not working well, seen from the following indicators: first, local governments do not get and run the rights and obligations under the Law No. 32 of 2004; Second, in terms of guidance or personnel management, has not run well because personnel guidance, nationally regulated and not give the functions of guidance to the Local Government; Third, in terms of the functions of supervision and guidance, the Local Parliament  is no longer functioning because the monitoring function has been taken over by the Central Government. This authority should be held by the Local Parliament as a representation in the local community. The method used is descriptive-qualitative method that is intended to describe an event in more detail.Key Words: Local Government, Local Autonomy, Local Authority